Transient ischemic attacks and small strokes. Modern therapeutic strategies - E. A. Shirokov; V. B. Simonenko; Yu. V. Ovchinnikov (Лечащий Врач)
Transient ischemic attacks (TIA) are a strong predictor not only of acute cerebral circulatory disorders, but also of other vascular events, including acute coronary syndrome and arterial thrombosis of other localization. Current clinical guidelines do not distinguish between TIA and small ischemic stroke in terms of treatment strategy. Meanwhile, the high probability of intracranial hemorrhages in patients with small strokes and small artery disease limits the possibility of aggressive therapy in patients with TIA. This contradiction can be resolved if TIA is assessed as an emergency condition similar to acute coronary syndrome. Modern methods of brain imaging solve the problem of differential diagnosis between TIA and small strokes. Aggressive therapy with antiplatelet agents, antihypertensive agents, and statins reduces the likelihood of fatal vascular events in patients with TIA.